Asetosilasi Terpentin Indonesia Menggunakan Katalis Asam Sulfat - Diana Diana; Arief Budiman (Faculty of Industrial Technology Universitas Islam Indonesia, 2018)
Indonesia is one of the largest turpentine producing countries in the world. Turpentine is one type of essential oil whose main component is alpha pinene. Alpha pinene is a bicyclic terpene that can undergo various reactions. This research aims to study the reaction process of turpentine acetoxylation using sulfuric acid catalyst. The reaction is carried out using glacial acetic acid and acetic acid solution. The experiments were run in a batch reactor for 2 hours at a constant temperature. Samples are taken to be analyzed using gas chromatography (GC). From the analysis it was found that the products included esters, isomers, and monocyclic alcohols. The use of acetic acid solution will significantly increase the monocyclic alcohol yield. The ratio of alpha pinene and acetic acid affects the conversion and product selectivity. While the purity of alpha pinen has no effect on the conversion achieved, but affects the selectivity of the resulting product.